2018
DOI: 10.21037/jtd.2018.01.91
|View full text |Cite
|
Sign up to set email alerts
|

Automatic detection of mycobacterium tuberculosis using artificial intelligence

Abstract: Background: Tuberculosis (TB) is a global issue that seriously endangers public health. Pathology is one of the most important means for diagnosing TB in clinical practice. To confirm TB as the diagnosis, finding specially stained TB bacilli under a microscope is critical. Because of the very small size and number of bacilli, it is a time-consuming and strenuous work even for experienced pathologists, and this strenuosity often leads to low detection rate and false diagnoses. We investigated the clinical effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(66 citation statements)
references
References 1 publication
2
47
0
Order By: Relevance
“…The investigators used a Gaussian model to apply various techniques that filter background interference, with a precision of >90%. Additionally, a study in China used a convolutional neural network model to recognize tuberculosis bacillus; this study used 201 samples for the test set, and the results were confirmed by pathologists, finding a sensitivity of 97.94% and a specificity of 83.65% (17).…”
Section: Discussionmentioning
confidence: 84%
“…The investigators used a Gaussian model to apply various techniques that filter background interference, with a precision of >90%. Additionally, a study in China used a convolutional neural network model to recognize tuberculosis bacillus; this study used 201 samples for the test set, and the results were confirmed by pathologists, finding a sensitivity of 97.94% and a specificity of 83.65% (17).…”
Section: Discussionmentioning
confidence: 84%
“…The investigators used a Gaussian model to apply various techniques that filter background interference, with a precision of >90%. Additionally, a study in China used a convolutional neural network model to recognize tuberculosis bacillus; this study used 201 samples for the test set, and the results were confirmed by pathologists, finding a sensitivity of 97.94% and a specificity of 83.65% (16).…”
Section: Discussionmentioning
confidence: 84%
“…The NIAID extramural portfolio of grants and contracts supports all aspects of TB research, ranging from studying the basic biology of Mycobacterium tuberculosis and its interaction with the host to investigating the various manifestations of TB (pulmonary, extrapulmonary, and latent) in adult and pediatric populations, including HIV-coinfected individuals, to conducting research aimed at developing new health care interventions. [9] Total of 66 MDR TB patients started treatment, from the study population and among them 20 (30%) were resistant to one or more second line drugs including a case of "XDR TB". For treatment only half of the patients The genome sequences including positions outside 23 genes and deep networks for nonlinear classification and dimension reduction and also optimising the number of SPCA/SNMF components can be considered as the future work.…”
Section: Related Workmentioning
confidence: 99%